2011
DOI: 10.1152/ajpgi.00058.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of interleukin-18: inhibiting hepatitis B virus replication in HepG2.2.15 cells and promoting hepatoma cells metastasis

Abstract: Interleukin-18 (IL-18) has been reported to inhibit hepatitis B virus (HBV) replication in the liver of HBV transgenic mice; however, the molecular mechanism of its antiviral effect has not been fully understood. In the present study, it was shown that IL-18 and its receptors (IL-18R) were constitutively expressed in hepatoma cell lines HepG2 and HepG2.2.15 as well as normal liver cell line HL-7702. We demonstrated that IL-18 directly inhibited HBV replication in HepG2.2.15 cells via downregulating the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…IL18 has prometastatic effects in melanoma patients and may promote clinical aggressiveness of human myeloid leukemia (13). IL18 also promoted hepatoma cell metastasis and migration (25). We found that IL18 promoted the proliferation and invasion of pancreatic cancer cells in vitro and in vivo but had no effect on apoptosis, drug resistance, or stem cell-like properties in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 71%
“…IL18 has prometastatic effects in melanoma patients and may promote clinical aggressiveness of human myeloid leukemia (13). IL18 also promoted hepatoma cell metastasis and migration (25). We found that IL18 promoted the proliferation and invasion of pancreatic cancer cells in vitro and in vivo but had no effect on apoptosis, drug resistance, or stem cell-like properties in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 71%
“…This inhibitory effect by IL-18 could be rescued by the administration of BAY11-7082, an inhibitor of transcription factor NF-κB. Furthermore, it was confirmed that expression of IL-18/IL-18R were remarkably up regulated in hepatocellular carcinoma (HCC) liver cancer tissue specimens, suggesting that IL-18 is involved in HCC metastasis in addition to its suppressive effect on HBV replication [11,12].…”
Section: Introductionmentioning
confidence: 82%
“…Since IL-18-stimulated IFN-␥ has direct antiviral effects against HBV and activation of IL-18 signaling decreases HBV replication in hepatocytes (14), it is not surprising that HBV evolved mechanisms to regulate IL-18 signaling and IFN-␥ expression. HBV utilizes numerous mechanisms to regulate other innate immunity signaling pathways, including HBeAg and precore protein-mediated regulation of TLR2 (5, 6) and IL-1␤ (7), with the latter sharing a number of salient features with IL-18 signaling (33).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which HBV establishes and maintains chronic infection are still to be resolved. However, recent findings that NK cell-driven IFN-␥ responses are lower in CHB patients with high HBV viral loads (16) and that upregulation of IL-1 or the related IL-18 signaling inhibits HBV replication in hepatocytes (4,14) suggests that regulation of IL-18 is one mechanism by which HBV facilitates persistence. This is further supported by our findings that suppression of IFN-␥ expression by NK cells is directly mediated both by factors present in serum from HBeAgpositive CHB patients and by the HBeAg protein itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation